Navigating the Landscape of Islamic FinTech: A Comprehensive Literature Review - Rani, Asni Mustika; Purnomo, Budi Supriatono; Purnamasari, Imas (The Eastasouth Management and Business, 2024)
The primary objective is to provide a comprehensive understanding of the current state and potential growth of Islamic FinTech in Indonesia. Specifically, the study delves into the impact of the COVID-19 pandemic, regulatory considerations, and the role of Sharia principles in shaping the Islamic FinTech landscape. Employing bibliometrics, literature review, and content analysis, the study examines Scopus-indexed documents related to Islamic FinTech. The research uses VOSViewer for network analysis, providing insights into research trends, influential articles, and keyword co-occurrence, thereby contributing to the existing literature on Islamic FinTech. The study identifies four thematic clusters in the global distribution of Islamic FinTech research: (1) Islamic FinTech, (2) Islamic finance, (3) technology, and (4) Islamic economics. Additionally, the research illustrates the surge in Islamic FinTech publications since 2018, indicating growing global interest. Noteworthy is Indonesia's substantial contribution to Islamic FinTech research, reflecting the country's emergence as a significant player in this domain.